2005
DOI: 10.1063/1.2112204
|View full text |Cite
|
Sign up to set email alerts
|

High-power single-mode vertical-cavity surface-emitting lasers

Abstract: This letter reports a design for high-power single-mode operation in vertical-cavity surface-emitting lasers by means of modal gain control using two different sized current apertures to shape the injection-current profile. A smaller current aperture is located several mirror-pairs away from the active region in the p-mirror and a larger current aperture is located in the first n-mirror-pair next to the active region. Both theoretical modeling and experimental test results show substantial improvement in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…However, the second aperture is located relatively far from the active region. Nevertheless, Samal et al [35] have observed single-fundamental-mode operation of their VCSELs with two oxide apertures, whereas their VCSEL with only one oxide aperture located close to the antinode position emits the high-order LP 31 transverse mode, which is consistent with our model.…”
Section: Simulation Of Oxide-confined Vcselssupporting
confidence: 81%
See 1 more Smart Citation
“…However, the second aperture is located relatively far from the active region. Nevertheless, Samal et al [35] have observed single-fundamental-mode operation of their VCSELs with two oxide apertures, whereas their VCSEL with only one oxide aperture located close to the antinode position emits the high-order LP 31 transverse mode, which is consistent with our model.…”
Section: Simulation Of Oxide-confined Vcselssupporting
confidence: 81%
“…Our theoretical model of the proposed SCO VCSEL configuration is consistent with the experimental work by Samal et al [35]. As in the SCO VCSEL, two apertures of different diameters on both sides of the VCSEL active region are utilized leading to dramatically improved mode selectivity.…”
Section: Simulation Of Oxide-confined Vcselssupporting
confidence: 74%
“…Dynamic of the VCSELs is primarily governed by the following space and time dependent rate equations coupled with thermal equation as follows (Jungo and Erni, 2003;Samal, 2004):…”
Section: Coupled Thermal Equation and Rate Equationmentioning
confidence: 99%
“…The modification of Equation (5) begins with separation of the time and space variables. This is done for photon density by describing as azimuthal and radial components of the optical field so-called c and s modes (Jungo and Erni, 2003;Samal, 2004):…”
Section: Coupled Thermal Equation and Rate Equationmentioning
confidence: 99%
See 1 more Smart Citation